2007
DOI: 10.1111/j.1532-5415.2007.01083.x
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Evaluation of a Nursing Home Fall Management Program

Abstract: Implementation was associated with significantly improved care process documentation and a stable fall rate during a period of substantial reduction in the use of physical restraints. In contrast, fall rates increased in NHs owned by the same organization that did not implement the FMP. The FMP may be a helpful tool for NHs to manage fall risk while attempting to reduce physical restraint use in response to the Centers for Medicare and Medicaid Services quality initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
2
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 29 publications
0
73
2
5
Order By: Relevance
“…Moreover, positive effects have been demonstrated on accidental falls. 59 Finally, the Evercare APN Most outpatients required only 1 follow-up appointment (n ¼ 64), 20 returned for 2 sessions and 5 attended 5-session limit; follow-up mean score for psychological distress (K-10) decreased by 2 categories (from very high to moderate with statistically significant improvement on all items, P < .001); small improvement on General Self-Efficacy Scale and modest association between a decrease in psychological distress and improvement in perceived selfefficacy (P ¼ .0137) GDS, Geriatric Depression Scale; PCS, Physical Component Summary, SF-12: Short Form health surveye12 items. program in US nursing homes showed a halving of hospital admissions with a savings of $103,000 per year per nurse practitioner.…”
Section: The Impact Of Advanced Practice Nursing In Primary Carementioning
confidence: 97%
“…Moreover, positive effects have been demonstrated on accidental falls. 59 Finally, the Evercare APN Most outpatients required only 1 follow-up appointment (n ¼ 64), 20 returned for 2 sessions and 5 attended 5-session limit; follow-up mean score for psychological distress (K-10) decreased by 2 categories (from very high to moderate with statistically significant improvement on all items, P < .001); small improvement on General Self-Efficacy Scale and modest association between a decrease in psychological distress and improvement in perceived selfefficacy (P ¼ .0137) GDS, Geriatric Depression Scale; PCS, Physical Component Summary, SF-12: Short Form health surveye12 items. program in US nursing homes showed a halving of hospital admissions with a savings of $103,000 per year per nurse practitioner.…”
Section: The Impact Of Advanced Practice Nursing In Primary Carementioning
confidence: 97%
“…Make sure staff get message about importance of standand-pivot technique. a shift toward interventions that are multifactorial; this shift is justified by our model, which incorporated process and systems changes [43][44][45][46]. For the most part, study participants identified numerous low-or no-cost solutions to address risk factors and failures identified in the model.…”
Section: Behaviormentioning
confidence: 99%
“…Evaluations of FMP found improved documentation of care processes related to falls management and a greater reduction in physical restraint use in intervention NHs. They also found that control NHs experienced a slight increase in fall rates following restraint reduction, but intervention NHs experienced no change in fall rates (69).…”
Section: Importance As a Quality Indicatormentioning
confidence: 93%